Repeatability of scores on a novel test of endurance running performance - Rollo, I.; Williams, C.; Nevill, A. (Journal of Sports Sciences, 2008)
The aim of the present study was to determine the repeatability of a running endurance test using an automated treadmill system that requires no manual input to control running speed. On three separate occasions, 7 days apart, 10 experienced male endurance-trained runners (mean age 32 years, s = 10; VO2peak 61 ml/kg·min, s = 7) completed a treadmill time trial, in which they were instructed to run as far as possible in 60 min. The treadmill was instrumented with an ultrasonic feedback-controlled radar modulator that spontaneously regulated treadmill belt speed corresponding to the changing running speed of each runner. Estimated running intensity was 70% VO2peak (s = 11) and the distance covered 13.5 km (s = 2), with no difference in mean performances between trials. The coefficient of variation, estimated using analysis of variance, with participant and trial as main effects, was 1.4%. In summary, the use of an automated treadmill system improved the repeatability of a 60-min treadmill time trial compared with time trials in which speed is controlled manually. The present protocol is a reliable method of assessing endurance performance in endurance-trained runners.